The Effectiveness of Turmeric Extract (Curcuma domestica Val.) Against Fibroblast Cells in Socket Post Tooth Extraction - Lokanata, Shieny; Sendyra Utama; Mellisa Sim (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. This study is an exploration to assess the potential of turmeric extract in the induction of fibroblast cell proliferation, where fibroblast cells are important cells in the process of repair and healing of wounds (socket wounds after tooth extraction). The antioxidants found in turmeric extract are believed to have potential in the initiation of growth factors which will then initiate the process of fibroblast cell activation, which in turn will play a role in wound healing. Methods. The research design in this study is an experimental study with a post-test-only approach with a control group design. The research subjects in this study were rats (Rattus norvegicus) Wistar strain, male sex, age 8-12 weeks, and body weight between 150-250 grams. A total of 30 white rats were grouped into 5 groups. Data analysis was carried out with the help of SPSS 25 software. First, a univariate analysis was performed to present the mean number of fibroblast cells and the standard deviation. Furthermore, an analysis was carried out to assess the difference in the mean number of fibroblast cells between groups using the one-way ANOVA test. Results. The results of the one-way ANOVA test showed that there were significant differences between the test groups. Giving 10% and 15% turmeric extract was seen to be more potent in the initiation of the number of fibroblast cells than the treatment group that received povidone-iodine. Conclusion. Turmeric extract (Curcuma domestica Val.) concentration of 15% was the most effective concentration as an effort to increase the number of fibroblast cells after tooth extraction in Wistar rats.